Pillars of creation : how the James Webb Telescope unlocked the secrets of the cosmos - Panek, Richard (Little, Brown and Company, 2024)
"The James Webb Space Telescope is transforming the universe right before our eyes--and here, for the first time, is the inside account of how the mission originated, how it performs its miracles of science, and what its revolutionary images are revealing." --